DOCUMENTATION AND ANALYSIS OF THE DAWAT CULTURAL JOURNAL: HISTORICAL AND DISCOURSE STUDY OF RIAU MALAY CULTURE - Rosman H; Alvi Puspita; Tengku Muhammad Sum (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to document and analyze Jurnal Kebudayaan Dawat as an intellectual archive that reflects the dynamics of Malay cultural thought in Riau during the 1990s. Using a qualitative approach and cultural discourse analysis, the research integrates Hall’s (1997) theory of representation, Fairclough’s (2010) critical discourse framework, and McLuhan’s (1994) concept of media and culture. Data were collected through archival tracing, interviews, and digitalization of four Dawat editions (1994–1996) published by the Center for Malay Language and Cultural Studies, University of Riau. The findings reveal that Dawat functioned as a space of representation and decolonization of knowledge, highlighting three main thematic axes: Malay identity and marwah, oral tradition and literature, and intellectualism and history. The digital preservation of Dawat represents not merely a technical act but an epistemological effort to sustain Malay intellectual heritage. This study emphasizes the importance of preserving local cultural sources through scholarly, collaborative, and technology-based approaches.